A variational derivation of a class of BFGS-like methods. (2nd November 2018) - Pavon, Michele
ABSTRACT: We provide a maximum entropy derivation of a new family of BFGS-like methods. Similar results are then derived for block BFGS methods. This also yields an independent proof of a result of Fletcher 1991 and its generalization to the block case.